THE TAN(F(z)/2-EXPANSION METHOD FOR THE SOME TRAVELING WAVE SOLUTIONS OF THE (2+1)-DIMENSIONAL BURGERS EQUATION - Ic, Unal (Editura Bibliotheca-Bibliotheca Publ House, 2020)
In this paper, we implemented a tan(F(z)/2-Expansion Method for traveling wave solutions of (2+1)-dimensional Burgers equation.
Keywords: (2+1)-dimensional Burgers equation; tan(F(z)/2-Expansion Method; Traveling wave solutions